2008
DOI: 10.1111/j.1365-2915.2008.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution and abundance of tsetse flies (Glossina spp.) in the Faro and Deo Division of the Adamaoua Plateau in Cameroon

Abstract: Ten years after the large-scale tsetse control campaigns in the important cattle rearing areas of the Faro and Deo Division of the Adamaoua Plateau in Cameroon, the seasonal distribution and abundance of tsetse flies (Glossina spp.) were determined. During a period of 12 consecutive months (January-December 2005), the tsetse population was monitored along four trap transects consisting of a total of 32 traps and two flyround transects traversing the study area, which comprised the tsetse-infested valley, a buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…The relative densities of G. m. submorsitans for the three main trap sites (Nguemfiti, Kontcha and Benoue National Park) were estimated at 9.6, 7.4 and 3.7 flies/ trap/day, respectively. These densities were superior to the index of apparent abundance reported by Mamoudou et al [31] for other villages in the same region where the present study was undertaken. The differences may simply be due to differences in biotopes as our study sites were more remote and inaccessible than those of MaCopyright © 2013 SciRes.…”
Section: Resultsmentioning
confidence: 42%
See 2 more Smart Citations
“…The relative densities of G. m. submorsitans for the three main trap sites (Nguemfiti, Kontcha and Benoue National Park) were estimated at 9.6, 7.4 and 3.7 flies/ trap/day, respectively. These densities were superior to the index of apparent abundance reported by Mamoudou et al [31] for other villages in the same region where the present study was undertaken. The differences may simply be due to differences in biotopes as our study sites were more remote and inaccessible than those of MaCopyright © 2013 SciRes.…”
Section: Resultsmentioning
confidence: 42%
“…During a longitudinal study in the Adamawa region it was found that the incidence of trypanosomosis was high in the valley (3.7% -20%) and the buffer zone (1.8% -13.4%), and was significantly lower (0% -2.1%) on the plateau where tsetse clearing had previously been undertaken [31]. They also caught mainly Glossina morsitans submorsitans and a few G. tachinoides in the valley and the buffer zone, but none on the plateau and concluded that the distribution of tsetse, in a large part of the valley, undergoes substantial seasonal changes depending on either the presence or absence of cattle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…morsitans submorsitans , and G . tachinoides [51]. Preventive and curative trypanocidal drugs were administered to cattle by government services from 1960 to 1975 in the regions of Adamawa, East and North.…”
Section: Resultsmentioning
confidence: 99%
“…The vegetation in this area is diversified, with two main groups of bushlands dominated by Daniellia oliveri and Lophira lanceolata covering the Plateau of Adamaoua [20]. Rivers present in this area harbor gallery forests infested by two tsetse species: Glossina morsitans submorsitans and Glossina tachinoides [21]. Up to 7 tick species are also present with Rhipicephalus (Boophilus) decoloratus and Amblyomma variegatum as principal abundant species [22].…”
Section: Methodsmentioning
confidence: 99%